Surrogacy in Portugal: drawing insights from international practices - CONDE, Ana; Santos PEREIRA, Carla; DIAS COSTA, Eva; ARAÚJO, Maria; DOMINGUES, Mariana; PINHO, Micaela; MARTINEZ DE CAMPOS, Mónica; ARAÚJO, Rita; JAYANTITAL, Shital (Revista Jurídica Portucalense, 2024)
As Portugal prepares to implement surrogacy legislation, it enters a realm fraught with legal, ethical, and psychological complexities. Across the globe, jurisdictions exhibit diverse approaches to surrogacy, reflecting cultural, ethical, and legal diversity. This necessitates a comprehensive understanding of the implications of surrogacy within different legal systems. Moreover, the psychological impact on surrogates, intended parents, and offspring demands careful examination. As Portugal embarks on this journey, it must navigate ethical challenges, ensuring the protection of all parties involved. Furthermore, addressing research gaps and ethical dilemmas will be paramount in crafting legislation that upholds the rights and well-being of all individuals affected by surrogacy arrangements.